A ordem dos exercícios resistidos não influencia parâmetros autonômicos e hemodinâmicos em idosas - COSTA, Laissa Lima da (2018)
Introduction: Impact of increasing age on the cardiovascular system results in the appearance of hemodynamic and autonomic balance dysfunctions leading to a reduction in heart rate variability (HRV) as well as changes in blood pressure (BP) values that culminate in the development of arterial hypertension. Resistance training is recommended as an alternative prevention and complementary to the treatment of hypertension and other cardiovascular disorders. And among the training variables, the order of exercise has shown better physiological responses, when more muscle mass is recruited at the beginning of the training session. Purpose: To analyze the effect of exercises order on the hemodynamic and autonomic parameters in elderly women. Materials and Methods: The sample consisted of 10 elderly women with 68.0 ± 3.5 years, body mass of 65.40 ± 3.3 kg and height of 150.00 ± 5.0 centimeters; Systolic BP 129.50 ± 20.2 mmHg and diastolic BP 76.70 ± 7.6 mmHg. Two sequences of resistive exercises for upper limbs were used: Sequence A – Bench Press, Pull Down, Shoulder Press, Barbell Curl and Triceps Pulley; Sequence B – constituted in reverse order. The training sessions were composed of 3 series with load corresponding to 80% of 10 RM, until failure, with interval of two minutes between each series and exercises. The hemodynamic measurements were collected by a digital monitor, OMRON brand. The HRV was measured by the cardiofrequency meter, model RS800CX. Results: After exercise, systolic blood pressure was higher in both exercise sequences, and there was no significant difference between sequences, as well as in the other hemodynamic parameters. There was an increase from the pre-moment to the post-moment in both groups. In addition, no diferences in heart rate variability were observed when compared the two orders. Conclusion: The physiological stress generated by the exercise reflected in sympathetic activation, but no significant difference was observed between the exercise protocols on the studied variables.